Effects of blood flow on the antibacterial efficacy of chlorhexidine and silver sulfadiazine coated central venous catheter: A simulation-based pilot study. Issue 39 (25th September 2020) - Cui, Yong Huan; Choi, Yoon Ji; Kim, Eung Hwi; Yu, Joon Ho; Seong, Hyun Young; Choi, Sung-uk; Yoon, Seung Zhoo; Huh, Hyub
Abstract: Background: Chlorhexidine and silver sulfadiazine coated central venous catheters (CSS-CVC) may cause loss of antimicrobial efficacy due to friction between the CVC surface and sheer stress caused by the blood flow. Therefore, the aim of this study was to investigate the antibacterial efficacy of CSS-CVC at various flow rates using a bloodstream model. Methods: Each CVC was subjected to various flow rates (0.5, 1, 2, and 4 L/min) and wear-out times (0, 24, 48, 72, 96, and 120 hours), and the optical density (OD) 600 after a Staphylococcus aureus incubation test was used to determine the antibacterial effect of CSS-CVC. Results: In the 0.5 L/min group, there was no significant change in the OD600 value up to 120 hours compared with the baseline OD600 value for CSS-CVC ( P  > .467). However, the OD600 values of CSS-CVC in the 1 L/min ( P  < .001) and 2 L/min ( P  < .001) groups were significantly reduced up to 72 hours, while that in the 4 L/min ( p  < 0.001) group decreased rapidly up to 48 hours. Conclusion: This study suggests that there is a doubt whether sufficient antibacterial function can be maintained with prolonged duration of catheter placement.